2023
DOI: 10.1101/gad.350278.122
|View full text |Cite
|
Sign up to set email alerts
|

A model for Scc2p stimulation of cohesin's ATPase and its inhibition by acetylation of Smc3p

Abstract: The evolutionarily conserved cohesin complex mediates sister chromatid cohesion and facilitates mitotic chromosome condensation, DNA repair, and transcription regulation. These biological functions require cohesin's two ATPases, formed by the Smc1p and Smc3p subunits. Cohesin's ATPase activity is stimulated by the Scc2p auxiliary factor. This stimulation is inhibited by Eco1p acetylation of Smc3p at an interface with Scc2p. It was unclear how cohesin's ATPase activity is stimulated by Scc2p or how acetylation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Finally, Boardman et al (2023) found further support for their model with the demonstration that the in vitro ATPase activity of Smc3-K113Q complexes cannot be stimulated by Scc2, but that Smc1-T1117I causes an increase in ATPase activity. In contrast, Smc1-T1117W displays lower activity.…”
mentioning
confidence: 61%
See 4 more Smart Citations
“…Finally, Boardman et al (2023) found further support for their model with the demonstration that the in vitro ATPase activity of Smc3-K113Q complexes cannot be stimulated by Scc2, but that Smc1-T1117I causes an increase in ATPase activity. In contrast, Smc1-T1117W displays lower activity.…”
mentioning
confidence: 61%
“…Smc3 acetylation blocks loading and loop extrusion, thereby anchoring loops and stabilizing cohesion. Boardman et al (2023) provide genetic evidence that Scc2 modulates ATPase activity through interactions with Smc1 and that these interactions are blocked by Smc3 acetylation. Note that Scc3 is not shown for simplicity.…”
mentioning
confidence: 88%
See 3 more Smart Citations